Tobit : the Book of Tobit in Codex Sinaiticus - Littman, Robert J., 1943- (Septuagint Commentary Series., 2008)
Tobit is one of the Apocrypha, a collection of books rejected from their canon by the Jews but accepted by some of the Christian church fathers. Ever since the 4th century CE, commentaries have been written on Tobit. The original Hebrew and Aramaic versions of Tobit were lost, until fragments were discovered as part of the Dead Sea Scrolls in 1947. The present work is the first Greek text and commentary of Tobit to be published since the publication of the Hebrew and Aramaic fragments. This edition contains the text from two fourth century CE manuscripts, the Codex Sinaiticus (long version) and Codex Vaticanus (short version) as well as a translation into English and a commentary.